Pollination of Adenocalymma bracteatum (Bignoniaceae): Floral biology and visitors - Almeida-Soares, Stela (2010)
Adenocalymma bracteatum is a shrub of dense foliage and yellow fl owers, easily found on grasslands areas in Central Brazil. The aim of this study was to determine the reproductive biology and the fl ower visitors of A. bracteatum in a pasture area nearby Ivinhema city, MS (Brazil). The fl owering peak occurs in winter. The fl ower refl ects ultraviolet light. Anthesis begins at 6:30h, and pollen and nectar are the resources to visitors. We captured 1,038 fl oral visitors. The bees Apis mellifera (L.), Trigona sp., Trigona spinipes (Fabricius), (Hymenoptera: Apoidea) and the ant Cephalotes sp. (Hymenoptera: Formicidae) were the main visitors. The reproductive tests indicate that A. bracteatum is self compatible, justifying its expansion in altered environments; however, the largest reproductive success was dependant on cross-pollination and self-pollination, evidencing the pollinators importance. Adenocalymma bracteatum presents melittophilous syndrome and bumblebees were the main pollinators in the area. The correlations observed between the climatic variables and the main pollinator species were low or medium.